Kombinasi Dosis Pemupukan dan Frekuensi Sadap terhadap Produktivitas Individu Tanaman Karet - Aji, Yoga Bagus Setya; Nugrahani, Mudita Oktorina; Putra, Riko Cahya (Jurnal Agro Industri Perkebunan, 2023)
Fluctuating rubber prices cause rubber planters to suffer losses, especially when prices are low as of right now. Planters apply high-intensity tapping to obtain maximum production but this is not balanced with optimal fertilization and actually has a negative impact on the sustainability of rubber plantations. The purpose of this study was to determine the effect of a combination of fertilizing doses and tapping frequency on the productivity of rubber plants and to obtain optimal fertilizer doses and tapping frequency when rubber prices are low. The research method used a randomized block design (RBD), with six combination treatments of tapping frequency and fertilization. The results showed that the highest volume of latex was produced in the S/2 d3 ET treatment of 2.5% 100% fertilization, while the variable dry rubber content (DRC), tapping frequency treatment d3 (B, D, F) produced higher DRC and was significantly different compared to tapping frequency treatment d2 (A, C, E). The highest KKK was obtained in treatment F, namely 38.6%. Observation of individual plant production (g per tree per tapping), 50% - 100% fertilization treatment can increase the production of both tapping frequency d2 and d3. The highest production was obtained in treatment F (S/2 d3 ET2.5% 100% fertilization). So, tapping with d3 tapping frequency combined with 100% fertilization dose produces the highest individual plant productivity. Tapping with d3 frequency combined with 50% fertilization can be an alternative when the rubber price is low.